Information technology : metadata registries (MDR) part 1 framework = Technologies de l'information. Registres de métadonnées (RM) : Partie 1: Cadre de référence (ISO/IEC, 2015)
ISO/IEC 11179 addresses the semantics of data, the representation of data and the registration of the descriptions of that data. It is through these descriptions that an accurate understanding of the semantics and a useful depiction of the data are found.